An Innovative Project-Based Active Learning Model with Scientific Literacy for Enhancing HOTS - Christina Sitepu; Manihar Situmorang; Saronom Silaban (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2026)
Higher-order thinking skills (HOTS) are essential for scientific problem-solving and lifelong learning; however, General Chemistry instruction in higher education is often lecture-centered and insufficient in fostering cognitive engagement and scientific literacy. This study develops and evaluates an project-based active learning model with scientific literacy to enhance students’ HOTS. Using a mixed-methods Research and Development approach with a sequential explanatory design, the study involved needs analysis, development of scientific literacy–based mini-projects on chemical bonding and acid–base solutions, instructional design, and model implementation. Quantitative data were analyzed using SEM-PLS. The measurement model demonstrated adequate convergent and discriminant validity (AVE > 0.50) and high internal consistency. The structural model showed a strong and significant effect of project-based active learning model with scientific literacy on HOTS (path coefficient = 0.911), with high explanatory and predictive power (R² = 0.911; Q² = 0.898). Learning motivation, engagement, self-regulated learning, instructional design quality, collaboration, and lecturer facilitation significantly contributed to HOTS. Scientific literacy strengthened the effects of several learning factors on HOTS. These findings indicate that integrating scientific literacy into project-based learning is effective strategy to improving HOTS in undergraduate General Chemistry.